Characterization of Focal Breast Lesions by Means of Elastography - Fischer, T.; Sack, I.; Thomas, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The modern method of sonoelastography of the breast is used for differentiating focal lesions. This review gives an overview of the different techniques available and discusses their roles in the routine clinical setting.Materials and Methods: The presented techniques include compression or vibration elastography as well as shear wave elastography. Descriptions of the methods are supplemented by a discussion of the clinical role of each technique based on the most recent literature. We discuss by outlining two recent experimental approaches – MRI and tomosynthesis elastography.Results: Currently available data suggest that elastography is an important supplementary tool for the differentiation of breast tumors under routine clinical conditions. The specificity improves with the immediate availability of additional diagnostic information using real-time techniques and/or the calculation of strain ratios (SR). Elastography is especially helpful in women with involuted breasts for differentiating BI-RADS-US 3 and 4 lesions and for evaluating very small cancers without the typical imaging features of malignancy. Here, elastography techniques are highly specific, while the sensitivity decreases compared to B-mode ultrasound. SR calculation is especially helpful in women who have a high risk of breast cancer and high pretest likelihood.Conclusion: B-mode ultrasound is still the first-line method for the initial evaluation of the breast. If suspicious findings are detected, elastography with or without SR calculation is the most crucial supplementary tool.Key Points:Citation Format:
Keywords: elastography; strain ratio; breast lesion; ultrasound; MRI